Production of bioprotein from palm pressed fibre by Aspergillus Terreus UniMAP AA-1 - Vijayakumaran, Yuvenesswari (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Demand in food source especially in protein is increasing globally. Due to expensive conventional protein and its raw material, cheaper carbon sources such as agricultural wastes were used to produce highly nutritious bioprotein in order to replace the conventional protein. Thus, in this research, palm pressed fibre from agricultural waste was used as substrate to obtain bioprotein. The purpose of this research is to develop a Plackett-Burman design for screening the affecting media composition in production of bioprotein. Besides, this study was also to optimize the protein production using Central Composite Design method where the most significant media composition was determined to increase the yield of bioprotein. Solid-state fermentation was done using 10 % of Aspergillus terreus UniMAP AA-1 from working volume of 12 g on the substrate for 5 days at 32 C The substrate was pre-treated with 5 % NaOH and 50 % moisture was maintained during fermentation. Protein and carbohydrate analysis were done everyday during fermentation process to obtain growth profile. Bioprotein produced on the fifth day was 4 times the first day of fermentation. Optimization of three parameters, NH4NO3, MgSO4.7H2O and FeSO4.7H2O from total of seven parameters was done. However, FeSO4.7H2O was not included during optimization as it was maintained at its maximum concentration which was 0 % (w/v). From the result, the optimum amount of NH4NO3 was 0.86 % (w/v) and MgSO4.7H2O was 0.07 % (w/v) to produce highest concentration of bioprotein that is 0.644978 mg/mL.